Activation of L-type Ca(2+) channels by protein kinase C is reduced in smooth muscle-specific Na(+)/Ca(2+) exchanger knockout mice - Ren, Chongyu (American Physiological Society, 2010)
L-type voltage-gated Ca(2+) channels (LVGCs) are functionally downregulated in arterial smooth muscle (SM) cells (ASMCs) of mice with SM-specific knockout of Na(+)/Ca(2+) exchanger type-1 (NCX1(SM−/−)) (32). Here, using activators and inhibitors of protein kinase C (PKC), we explore the regulation of these channels by a PKC-dependent mechanism. In both wild-type (WT) and NCX1(SM−/−) myocytes, the PKC activator phorbol 12,13-dibutyrate (PDBu) increases LVGC conductance, decreases channel closing rate, and shifts the voltage dependence of channel opening to more negative potentials. Three different PKC inhibitors, bisindolylmaleimide, Ro-31-8220, and PKC 19-31, all decrease LVGC currents in WT myocytes and prevent the PDBu-induced increase in LVGC current. Dialysis of WT ASMCs with activated PKC increases LVGC current and decreases channel closing rate. These results demonstrate that PKC activates LVGCs in ASMCs. The phosphatase inhibitor calyculin A increases LVGC conductance by over 50%, indicating that the level of LVGC activation is a balance between phosphatase and PKC activities. PDBu causes a larger increase in LVGC conductance and a larger shift in voltage dependence in NCX1(SM−/−) myocytes than in WT myocytes. The inhibition of PKC with PKC 19-31 decreased LVGC conductance by 65% in WT myocytes but by only 37% in NCX1(SM−/−) myocytes. These results suggest that LVGCs are in a state of low PKC-induced phosphorylation in NCX1(SM−/−) myocytes. We conclude that in NCX1(SM−/−) myocytes, reduced Ca(2+) entry via NCX1 lowers cytosolic [Ca(2+)], thereby reducing PKC activation that lowers LVGC activation.